2007
DOI: 10.1111/j.1365-2966.2007.11817.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiative torques: analytical model and basic properties

Abstract: We attempt to get a physical insight into grain alignment processes by studying basic properties of radiative torques (RATs). For this purpose we consider a simple toy model of a helical grain that reproduces well the basic features of RATs. The model grain consists of a spheroidal body with a mirror attached at an angle to it. Being very simple, the model allows analytical description of RATs that act upon it. We show a good correspondence of RATs obtained for this model and those of irregular grains calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
600
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 433 publications
(620 citation statements)
references
References 50 publications
18
600
2
Order By: Relevance
“…where QΓ is the RAT efficiency, which can be decomposed into three components Qe1, Qe2 and Qe3 in a scattering reference frame defined by unit vectorsê1,ê2,ê3 withê1 k,ê2 ⊥ê1 andê3 = e1 ×ê2 (Draine & Weingartner 1996;Lazarian & Hoang 2007a). In general, the magnitude of RAT efficiency QΓ depends on the radiation field, grain shape, size and its orientation relative to k. When the anisotropic direction of the radiation field is parallel to the axis of maximum moment of inertiaâ1, LH07 found that the magnitude of RAT efficiency can be approximated by a power-law as:…”
Section: Anisotropic Radiative Torquesmentioning
confidence: 99%
See 1 more Smart Citation
“…where QΓ is the RAT efficiency, which can be decomposed into three components Qe1, Qe2 and Qe3 in a scattering reference frame defined by unit vectorsê1,ê2,ê3 withê1 k,ê2 ⊥ê1 andê3 = e1 ×ê2 (Draine & Weingartner 1996;Lazarian & Hoang 2007a). In general, the magnitude of RAT efficiency QΓ depends on the radiation field, grain shape, size and its orientation relative to k. When the anisotropic direction of the radiation field is parallel to the axis of maximum moment of inertiaâ1, LH07 found that the magnitude of RAT efficiency can be approximated by a power-law as:…”
Section: Anisotropic Radiative Torquesmentioning
confidence: 99%
“…The quantitative study of RAT alignment was initiated in a series of papers, by our group, starting with Lazarian & Hoang (2007a) (henceforth LH07) where an analytical model of RAT alignment was introduced. The analytical model was the basis for further theoretical studies in (Lazarian & Hoang 2007b;, Hoang & Lazarian 2009bsee also reviews in Lazarian 2007;Lazarian, Andersson, & Hoang 2015;Andersson, Lazarian, & Vaillancourt 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Radiative alignment torque (RAT) theory has matured over the last decade and is now providing a number of specific, testable, predictions (Lazarian & Hoang 2007). One such prediction, which is especially attractive for probing the validity of the theory, since it is unique to RAT theory, is that the alignment efficiency, but not the polarization angle, should vary with the angle between the magnetic field and the radiation field anisotropy (Ψ; see Lazarian & Hoang 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Draine & Weingartner 1997;Lazarian & Hoang 2007). Based on early work by Dolginov & Mitrofanov (1976) they showed that an irregular grain with a net helicity will be spun up by the differential scattering of the left and right-hand circular components in an external light source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation